Integrated safety and process optimization approach for ammonia synthesis loop - Athar, M. (Universiti Malaysia Pahang, 2018)
Among the process safety strategies, inherent safety, proposed by Kletz, has been widely accepted and applied for the preliminary design of chemical processes. Process optimization with safety aspect has usually focused on accident costs rather than risk. Additionally, the significance of inherent assessment for process optimization has been overlooked. Simultaneous optimization of risk with inherent safety and process economics can be more impactful in practical process designs. Therefore, a new methodology is consolidated in this paper, such that an external risk and process economics model is coupled with HYSYS to achieve an optimized process design. Here, process stream index (PSI) has been suggested to identify the critical process streams. For identified critical process streams, risk analysis and process economics are studied. Risk estimation and process economics parameters are studied in an external model by extracting information from HYSYS through VBA coding. For unacceptable risk, minimization guide word is used to improve the performance of critical streams. With inherent safety implementation, process economics is also found to be improved, as 3.2 less energy would be required without any significant change in ammonia product quantity. This approach would serve to deal safety with process attributes as multi-objective optimization method of process design. Â© Universiti Malaysia Pahang, Malaysia.